Lipid metabolism modulation during SARS-CoV-2 infection : a spotlight on extracellular vesicles and therapeutic prospects - D’Avila, Heloisa (2024)
Extracellular vesicles (EVs) have a significant impact on the pathophysiological processes associated with various diseases such as tumors, inflammation, and infection. They exhibit molecular, biochemical, and entry control characteristics similar to viral infections. Viruses, on the other hand, depend on host metabolic machineries to fulfill their biosynthetic requirements. Due to potential advantages such as biocompatibility, biodegradation, and efficient immune activation, EVs have emerged as potential therapeutic targets against the SARS-CoV-2 infection. Studies on COVID-19 patients have shown that they frequently have dysregulated lipid profiles, which are associated with an increased risk of severe repercussions. Lipid droplets (LDs) serve as organelles with significant roles in lipid metabolism and energy homeostasis as well as having a wide range of functions in infections. The down-modulation of lipids, such as sphingolipid ceramide and eicosanoids, or of the transcriptional factors involved in lipogenesis seem to inhibit the viral multiplication, suggesting their involvement in the virus replication and pathogenesis as well as highlighting their potential as targets for drug development. Hence, this review focuses on the role of modulation of lipid metabolism and EVs in the mechanism of immune system evasion during SARS-CoV-2 infection and explores the therapeutic potential of EVs as well as application for delivering therapeutic substances to mitigate viral infections.